Simulation of stress wave attenuation in plain weave fabric composites during in-plane ballistic impact. (15th January 2017) - Pandya, Kedar S.; Kulkarni, Mandar D.; Warman, Anirudh; Naik, N.K.
Abstract: An analytical method is presented for the simulation of longitudinal stress wave attenuation in typical plain weave fabric composites made of E-glass/epoxy and T300 carbon/epoxy under in-plane ballistic impact. The stress wave propagation/attenuation simulation studies are carried out for the case of in-plane impact of projectiles on composite beam targets. Geometrical modeling of plain weave fabric composites and an algorithm for stress wave propagation/attenuation are presented. Studies are carried out for both free edge and rigid boundary conditions for different beams. Based on the analytical simulation, for typical plain weave E-glass/epoxy composite beams studied, it is observed that the stress intensity is about 5% of the incident value when the longitudinal stress wave reaches a distance of 110 mm from the point of in-plane impact at the representative section.